Recent Progress in Base-Metal-Catalyzed Dearomative Reaction of N-Heteroarenes - Ni, Qian; Chen, Yaqi; Ma, Yuanhong (Synthesis, 2025)
Three-dimensional nitrogen-containing heterocyclic compounds widely exist in many natural products and drugs. The dearomatization of N-heteroarenes and their derivatives have been recognized as one of the most important and powerful strategies for the rapid and efficient synthesis of various three-dimensional nitrogen-containing heterocyclic compounds. In this short review, the recent and representative advances in base-metal-catalyzed dearomatization of N-heteroarenes are summarized and discussed.1 Introduction2 Dearomatization of Indoles2.1 Copper Catalysis2.2 Nickel Catalysis2.3 Cobalt Catalysis2.4 Other Catalysts3 Dearomatization of Pyridines, Quinolines, Isoquinolines, and Pyrazine3.1 Copper Catalysis3.2 Nickel Catalysis3.3 Cobalt Catalysis3.4 Other Catalysts4 Summary and Outlook
Keywords: base metal catalysis; N-heterocycles; dearomatization; copper catalysis; nickel catalysis; cobalt catalysis